Top Chilean Business Schools: Discourses and Perceptions - Ibáñez, Manuel José (2015)
Several scholars have questioned the role and legitimacy of business schools as educational institutions. Other authors have criticized the mainstream definition of business as a science, and raised doubts about its practice as a profession. In this context, the present dissertation explores the relationship between the discourses of two top Chilean business schools and the perceptions of their alumni, with the intention of providing a new perspective about business education. Chile was selected due to the particular way in which extreme neoliberal reforms took place in the country during the second part of the nineteenth century (with the intervention of Chicago School) and because recent corporate scandals, involving alumni from top business schools, have highlighted the relevance of this institution. Two business schools were analysed: Pontifical Catholic University of Chile (owned by the Catholic Church) and University of Chile (owned by the secular state). A mixed methods approach was used: Discourse Analysis (DA) as a qualitative tool to understand the official discourses and statistical analysis for the perception of alumni. Information from official web pages and deans’ interviews were considered for the qualitative analysis, while an online survey was applied to alumni who studied during the last 45 years at both institutions. The study proposed a critical perspective of looking at business school education, contrasting school attributes (academic level, tools provided to serve society and shared vision/mission) and business attributes (good reputation, salary expectations and access to network) as incentives for entering the faculty. Neoliberal values (free market efficiency, finance, maximization of profits and economic theory) and altruistic values (business ethics, social commitment, corporate social responsibility and contribution to common good) were confronted and contrasted with the perceptions and suggestions from alumni. Results indicate that business schools tend to communicate the relevance of school attributes and altruistic values on their statements. However, both their curriculums and alumni’s perception suggest that neoliberal values have been playing a much more significant role. Most alumni state that school attributes were important while deciding to enter the business schools, jointly with the reputation of the faculty. Female alumni plead for the inclusion of topics related with altruistic values (especially business ethics) while UChile’s alumni result to be more prone towards neoliberal values. Finally, a few suggestions for Chilean business schools are offered, based on the literature and results of the analysis. Among them are increasing the diversity of academic staff and making efforts in developing dialogue with other actors, both inside and outside the university. At the same time, reforms to the curriculum will be needed to reflect a more holistic view regarding human nature and society, allowing business schools to better contribute to society as part of the university. Future research projects could continue with this work, in particular through the analysis of best ways to integrate altruistic values in curriculums, develop research with a wider vision about society and interact with alumni.